Significant simultaneous changes in serum CA19-9 and CA125 due to prolonged torsion of mature cystic teratoma of the ovary - Suh, Dong Soo (World J Surg Oncol, 2014)
Mature cystic teratoma is a common benign neoplasm of the ovary. Complications occur in approximately 20% of cases. Clinical manifestations, laboratory findings, and imaging studies can assist in making a diagnosis of ovarian torsion of mature cystic teratoma. Furthermore, serum tumor markers may be helpful for diagnosing mature cystic teratoma and its torsion and, thus, can lead to early surgical intervention. A 56-year-old woman presented with a huge pelvic mass and pelvic pain. Serum CA19-9, CA125, and carcinoembryonic antigen levels were abnormally elevated at >700 U/ml, 282.5 U/ml, and 3.94 U/ml, respectively. The tumor was surrounded by extensive adhesions and showed inflammatory changes. The serum levels of these markers returned to normal levels after surgery.